2020
DOI: 10.3389/fcell.2020.00776
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Model for Epidermal Growth Factor Receptor Ligand Binding Involving Conformational States of the Extracellular and the Kinase Domains

Abstract: The epidermal growth factor (EGF) receptor (EGFR) undergoes ligand-dependent dimerization to initiate transmembrane signaling. Although crystallographic structures of the extracellular and kinase domains are available, ligand binding has not been quantitatively analyzed taking the influence of both domains into account. Here, we developed a model explicitly accounting for conformational changes of the kinase and extracellular domains, their dimerizations and ligand binding to monomeric and dimeric receptor spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Previously, agonist-induced conformational models of the EGFR 38, 39 and the role of agonist binding kinetics in ligand bias have been described 40, 41 . For TK inhibitors, such studies are less well known, whereas it could improve understanding of their mode of action.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, agonist-induced conformational models of the EGFR 38, 39 and the role of agonist binding kinetics in ligand bias have been described 40, 41 . For TK inhibitors, such studies are less well known, whereas it could improve understanding of their mode of action.…”
Section: Discussionmentioning
confidence: 99%
“…The two major classes of these small molecule inhibitors differ in whether they recognize the active or inactive conformation of the KD [ 52 ]. Several studies found that type I inhibitors, stabilizing the active conformation of the kinase, increase the formation of EGFR dimers harboring inhibited KDs, while type II inhibitors, stabilizing the inactive kinase structure, inhibit homodimerization altogether [ 53 , 54 , 55 ]. However, lapatinib, a type II inhibitor, has been shown to latch ErbB2 into a conformation that predisposes it to form head-to-head KD dimers with ErbB3, which explains the unexpected synergy between this kinase inhibitor and heregulin in promoting cell proliferation [ 56 ].…”
Section: Dimerization-induced Activation Of Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…Several studies reported negative cooperative EGF binding curves [ 63 , 64 ], and these studies have been rationalized by linking negative cooperativity to the apparent heterogeneity of EGF binding sites [ 65 ], and by the observation of a squeezed, restrained ligand-binding site in the unliganded receptor in a singly liganded dimer in the Drosophila EGFR [ 66 ]. However, several findings put the issue into a different perspective, including the significant structural differences between how human and Drosophila EGFRs are activated [ 36 ], the loss of negative cooperative binding in studies of isolated, human EGFR ECDs [ 67 ], and the repeated observation of positive, cooperative ligand binding to EGFR [ 53 , 68 , 69 , 70 ]. It has been proposed that the inactive and active conformations of the KD are coupled to the tethered and untethered structures of the ECD, respectively, assumed to display different cooperativities [ 70 ].…”
Section: Dimerization-induced Activation Of Receptor Tyrosine Kinasesmentioning
confidence: 99%
See 2 more Smart Citations